Androgynous Selebgram Endorsement Influence Toward Consumer Buying Intention in Relation to The Instagram Advertisement for Fashion Product - Dermawan, Aril Rivai Ahmad; Wisesa, Anggara (Journal of Business and Management, 2020)
The topic of this research is about androgynous endorsement influence toward consumer buying intention on Instagram for fashion products. The problems involving androgyny who endorser on Instagram are very few due to stereotypes about those who are very biased, in Indonesia androgyny are having different interpretations because they display strange personalities in their eyes, even though the concept of androgyny is not limited to gender, many have done the androgyny concept, one of which is Thailand in that country has almost no point of view about gender. Androgynous fashion is the union of male and female style, as well as masculinity and femininity in one body. One example of the androgynous model in Indonesia is Jovi adhiguna, Jovi is an androgynous model that has long been engaged in the fashion world because it has an interest in fashion and fashion for men or women. Therefore, the purpose of this research is Identifying the effectiveness of androgyny models against endorsement Instagram affecting the consumer buying intention on using Instagram. Thus this research has two models, the first five aspects androgynous model (likeability, credibility, personality, attractiveness, and expertise) toward endorsement and endorsement toward consumer buying intention. The object of this research is knowing about how the influence of androgyny models on endorsement Instagram that affects consumer buying intention with the fashion of the advertised product. In the analysis using multiple linear regression (MLR). The questionnaire used in this research and for a sample consisting of (200) users of Instagram. For the result, the first model only one rejected because above 0.05 there is likeability, and the others are accepted because they have a value below 0.05 and the second model has a significant level for endorsement Influence toward consumer buying intention because they have a value below 0.05.